The influence of brand image, price and product quality on the purchase decision of skincare somethinc product - Melysa Rahmawati; Nur' Aeni (Institute of Computer Science (IOCS), 2023)
Industrial companies are currently experiencing developments in Indonesia, especially in the beauty or cosmetic industry. Because purchases of beauty products, including skincare this year, have increased by 16% compared to 2021 until now. Good skincare is skincare that is safe, comfortable and of good quality. In Indonesia, many local skincare brands are starting to develop. Many skincare products are made with different variants according to the skin needs of consumers who use them. This can be caused by several factors from Brand Image, Price, Product Quality and Purchase Decision. In this study using quantitative methods with a sample of 120 respondents. To be able to test the hypothesis in this study, the analytical method that will be used is Structural Equation Modeling (SEM), using LISREL 8.80. The hypothesis test used was a partial statistical test (t). Measurement model testing is carried out to see the validity and reliability of the dependencies of each development that builds the analysis model. The results of this study: (1) Brand Image Variables have a positive and significant influence on Purchasing Decision variables. The hypothesis in this study was accepted because of the results of the t test using Lisrel 8.80. (2) The price variable does not have a positive and significant effect on the decision to purchase somethink skincare products. The hypothesis in this study was rejected because it was based on the results of the t test using Lisrel 8.80. (3) The Product Quality Variable has a positive and significant influence on the Purchase Decision variable. The hypothesis in this study was accepted because of the results of the t test using Lisrel 8.80